Effects of audience, perceived ease of leaving, and in-group identification on the tendencies to favor or derogate the in-group. - Tan, Merrilyn Wan Wen. (2009)
This paper studies how audience, ease of leaving one’s in-group, and in-group identification would affect one’s degree of in-group derogation (IGD) and in-group favoritism (IGF). Word selections and essays describing Singaporeans were collected, as measures of IGD and IGF, from 120 Singaporean participants randomly assigned to one of four conditions (in-group audience, easy to leave; in-group audience, difficult to leave; out-group audience, easy to leave; out-group audience, difficult to leave). There is no interaction effect of ease of leaving and in-group identification on IGD and IGF across audiences. There is higher IGD with in-group audience than out-group audience, and higher IGF for high identifiers than low identifiers. Displays of IGD and IGF are dependent on individual and situational factors.